(untitled) (Kinesiology, 2018)
The aim of this study was to investigate the levels of motivation associated with participation in floorball (indoor hockey) and spinning, and how levels of motivation predicted continuation. A sample of 66 middleaged women participated in a 12-week intervention of either floorball or spinning. They filled out the Sport Motivation Scale in week 2 and week 11 of the intervention, and data on their continuation six and 12 months after the intervention was also collected. A repeated measures MANOVA showed that participants in the floorball group had higher levels of intrinsic and self-determined extrinsic motivation for the activity during the intervention period, suggesting that floorball is a more motivating activity. In addition, extrinsic motivation the introjected regulation increased in both groups during the intervention period. Intrinsic motivation, as well as extrinsic motivation introjected regulation, predicted participants’ continuation six and 12 months after the intervention, suggesting that motivation as viewed in a Self-Determination Theory perspective is important for continuation. Key words: exercise, fitness, motivation, psychology, team sport